Hand Dominance Effect During right (Accelerator) Throttle Gripping in Riding Simulation - Nasir, Nursalbiah; Hakimi Azmi, Asyraf; Rashid, Helmi (International Journal of Engineering and Technology, 2018)
This study investigated the difference in muscle activation of the muscles in right handed (RH) and left handed (LH) participants during riding of motorcycle simulator. Five participants (3 RH and 2 LH) with average age of 24.2Â±0.447 years old were recruited and they were requested to ride the simulator for certain period of times for three days. Two surface electromyogram (sEMG) electrodes were attached to right flexor carpi radialis (RFCR) and left flexor carpi radialis (LFCR) of the participants forearm. Electromyography (EMG) of flexor carpi radialis (FCR) are measured at both hands during the task. The results showed that muscle activation during first 5 minutes of riding task in day 1 of experiment (percentage of maximum voluntary contraction, %MVC) for RFCR in LH (non-dominant) participants was 97.4% and 87.7% in RH (dominant) participants. Therefore, this result indicates that non-dominant person needs to activate more muscle than RH person during control the accelerator throttle while riding.Â Â